Lesotho Post-Disaster Needs Assessment : Heavy Rains 2010-11 - Government of Lesotho (World Bank, Washington, DC, 2013)
The Kingdom of Lesotho is a land-locked nation located in the Drakensberg mountain range in Southern Africa. The country has a total area of 30355 km² and in 2009 had an estimated population of nearly 2.1 million, with nominal per capita Gross Domestic Product (GDP) of US$ 1080 (in 2010). About 75 percent live in rural areas, often in scattered mountain villages, while most of the urban population lives in and around the capital Maseru and the surrounding low lands. The hazards that affect Lesotho are drought, snowfall, hailstorms, strong winds, localized floods, and early frost. Lesotho's vulnerability to these hazards is compounded by a number of other underlying factors, including high levels of poverty, particularly in rural areas where the scattered nature of settlements makes the provision of and access to social services difficult. The high HIV prevalence rate has resulted in the existence of vulnerable groups, particularly Orphans and Vulnerable Children (OVCs). This document describes the implementation of the Post Disaster Needs Assessment (PDNA) process, presents the findings of the assessment and makes initial recommendations for post-disaster recovery, reconstruction and risk reduction activities, to be considered by the Government.